Os odontoideum associated with a retro-odontoid cyst treated with posterior C1–C3 fixation: A case report and literature review - Bao, Bei-Xi; Yan, Hui; Tang, Jia-Guang (Frontiers in Surgery, 2023)
Background: Os odontoideum is a rare abnormality of the upper cervical spine, and os odontoideum associated with a retro-odontoid cyst has been described as a marker of local instability [1,2]. Case description: This paper reports a case of a 52-year-old female patient who was diagnosed with os odontoideum associated with a retro-odontoid cyst. The patient underwent posterior C1–C3 fixation without surgical removal of the cyst. Magnetic resonance imaging (MRI) two days later revealed that the retro-odontoid cyst was still present and that there were no significant changes to it when compared with the preoperative MRI. Conclusion: Retro-odontoid cysts associated with unstable os odontoideum can lead to symptomatic spinal cord compression. Posterior C1–C3 fixation can restore atlantoaxial stability by allowing the gradual resorption of the cyst and ensuring spinal cord decompression. Fixation can also avoid the surgical risk associated with a high-riding vertebral artery.